Dynamic Analysis of Bulk Acoustic Wave Piezoelectric Micropumps: Effects of Inlet-Outlet Port Angles and Overall Pump Size - Sayar, Ersin; Farouk, Bakhtier (American Society of Mechanical Engineers, 2013)
Dynamic structural and fluid flow analysis of bulk acoustic wave piezoelectric valveless micropumps are carried out for the transport of water. The micropumps consist of trapezoidal prism inlet/outlet elements; the pump chamber, a thin structural layer and a piezoelectric element (PZT-5A), as the actuator. Governing equations for the flow fields and the structural-piezoelectric bi-layer membrane motions are considered. For the compressible flow formulation, an isothermal equation of state for the working fluid is employed. Two-way dynamic coupling of forces and displacements between the solid and the liquid domains in the systems are considered where actuator deflection and motion causes fluid flow and vice-versa. The effects of inlet-outlet port angles and overall pump size on the flow rate are investigated. The flow rate is found to increase with decreasing outlet convergence angle and increasing inlet divergence angle. In the second part of the present work, the size of the entire micropump is scaled to 50%, 100%, and 200% respectively while electrical parameters are kept constant.